Stunting death: affect, attraction and authenticity in Rated-R superhero cinema - Greene, Ryan Kent, author; Diffrient, David Scott, advisor; Burgchardt, Carl, advisor; Gravdahl, John, committee member (Colorado State University. Libraries, 2018)
Stunt work is an ever-present and typically overlooked aspect of film production. The labor goes unseen by design; traditionally, Hollywood studio hierarchies regarded a good stunt performer as one who altogether eluded audience detection. The early star system's stunt performers did not see their names splashed across film industry magazines as happens today. Even contemporarily, studios and surrounding paratextual discourse systematically de-emphasize the stunt even in cases where certain stunt performers become, as Lauren Steimer put it, "hypervisible." The trick works perhaps too well, as Steimer remains one of few scholars to studies stunts. Several of these few have called for stunt work's theoretical and generic expansion. The impetus for doing so is a fundamentally ethical one. How can a society view and engage with entertainment while being unaware of those who willingly risk injury and death to imbue films with authentic action? Stunt scholarship thus far has focused primarily on stunt worker's history—from their origins as human flies, bridge-jumpers and other daredevils to feckless circus clowns and all these characters' eventual absorption into Hollywood sets. Scholars also discuss ways in which stunt work complicates traditional understandings of film diegesis. I further articulate the stunt's relationship with diegetic narrative, tracing its functions through the cinema of attractions, avant-garde spectatorship, documentary space and other story-breaking constructs. In doing so, I hope to heed one particular scholarly call to evaluate this ubiquitous brand of labor within the brightly colored, ultra-violent and action-driven world of R-Rated superhero films. Fox studios recently produced two Deadpool (2016, 2018) films and Logan (2017). Critics hailed them as groundbreaking achievements within a genre that has typically eschewed not only fourth-wall-breaking humor, but gratuitous blood and gore. Something in the characters of Wade Wilson and old man Logan reflects common perceptions of stunt people. They must surely leap back up after any injury, much like the rapidly healing antiheroes they play in these films. Industry dialectic encourages a kind of spectatorship that does not linger on the stunt body's ethereal appearance on-screen. In removing attention from the stunt, such coverage tacitly preserves audience immersion in narrative while distracting attentions from the pain and sacrifice comprising the stunt performer's career. Since these performers give filmgoers authentic-looking affective thrills, I argue for a closer look at what is not meant to be seen.
Keywords: attraction; diegesis; stunts; authenticity; affect; narrative